Logistics and Supply Chain Innovation Bridging the Gap between Theory and Practice - Zijm, Henk.; Klumpp, Matthias; Clausen, Uwe.; Hompel, Michael ten.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This contributed volume presents  state-of-the-art advances in logistics theory in various fields as well as case studies. The book reports on a number of recently conducted studies in the Dinalog and the EffizienzCluster LogistikRuhr, thus bridging the gap between different perspectives of theoretical and applied research. A selection of theoretical topics, practical examples, case studies and project reports  is presented in this volume. The editors carefully selected contributions from a wide variety of projects, which were carried out in both the Dinalog cluster and the Effizienzcluster LogistikRuhr. The contributions are grouped in five main sections, each representing key domains in the evolution of logistics and supply chain management: sustainability, urban logistics, value chain management, IT-based innovation, knowledge management. This book is intended for both researchers and practitioners in the field of logistics and supply chain management, to serve as an important source of information for further research as well as to stimulate further innovation.
Logistics and Supply Chain Management: trends and developments -- . Synchromodal Transport Planning at a Logistics Service Provider -- DAVINC3I: Towards Collaborative Response Logistics Networks in Floriculture -- Towards Efficient Multimodal Hinterland Networks -- Current Deficiencies and Paths for Future Improvement in Corporate Sustainability Reporting -- Sustainable fuels for the transport and maritime sector: A Blueprint of the LNG distribution network -- Efficiency optimization for cold store warehouses through an electronic cooperation platform -- Urban Freight Transportation: Challenges, Failures and Successes -- The role of fairness in governing supply chain collaborations - a case-study in the Dutch floriculture industry -- Reducing the environmental impact of urban parcel distribution -- Order fulfillment and logistics considerations for multichannel retailers -- Connecting inventory and repair shop control for repairable items -- Knowledge lost in data: Organizational impediments to Condition-Based Maintenance in the process industry -- Planning Services: a Control Tower Solution for Managing Spare Parts -- Impediments to the adoption of reverse factoring for logistics service providers -- Towards an approach for long term AIS-based prediction of vessel arrival times.
Keywords: Industrial Management; Production management; Electronic data processing -- Management; Industrial Management; Operations Management; IT Operations